Language Style Used in Advertisements for Harper’s Bazaar Magazine: A Literary Study - Rugaiyah, Rugaiyah; Ismail, Syofianis (UIR Press, 2024)
This study investigates the language styles used in advertisements for Harper’s Bazaar magazine advertisements. The objective of the current study is to identify the stylistic features of magazine advertisements, particularly the stylistics features to provide valuable insights into how advertisers leverage linguistic and visual techniques to connect with their target audience and convey the essence of their brands. Understanding these stylistic strategies is not only valuable for advertisers and marketers but also for readers and consumers who engage with the content, making it an enriching exploration of the synergy between language, style, and fashion in the context of a prestigious British fashion magazine. The study was descriptive-qualitative and used documentation as the instrument. The data was taken from the September 2019 and April 2020 issues of